2009
DOI: 10.1111/j.1752-4571.2009.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza at both ends of a migratory flyway: characterizing viral genomic diversity to optimize surveillance plans for North America

Abstract: Although continental populations of avian influenza viruses are genetically distinct, transcontinental reassortment in low pathogenic avian influenza (LPAI) viruses has been detected in migratory birds. Thus, genomic analyses of LPAI viruses could serve as an approach to prioritize species and regions targeted by North American surveillance activities for foreign origin highly pathogenic avian influenza (HPAI). To assess the applicability of this approach, we conducted a phylogenetic and population genetic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…After sequencing, we detected five samples (7%) with mixed infections at the level of the surface glycoprotein genes and a total of 11 mixed infections (16%) when including those with mixed internal gene segments. One of these viruses, an H14 with 2 PA segments, has been previously reported (25). All mixed infections were detected in samples from blue-winged teals ( n = 10) with the exception of one which was detected in a sample from a green-winged teal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After sequencing, we detected five samples (7%) with mixed infections at the level of the surface glycoprotein genes and a total of 11 mixed infections (16%) when including those with mixed internal gene segments. One of these viruses, an H14 with 2 PA segments, has been previously reported (25). All mixed infections were detected in samples from blue-winged teals ( n = 10) with the exception of one which was detected in a sample from a green-winged teal.…”
Section: Resultsmentioning
confidence: 99%
“…Their internal gene segments were positioned in different subclades in the phylogenetic trees, indicating reassortment with other viruses. The introduction of this clade of Eurasian viruses has been previously documented in Alaska (26) and in California, albeit with limited circulation (25). This Eurasian-to-North America introduction occurred recently and is unrelated to the major incursion of Eurasian genes that occurred in the 1960s that gave rise to one of the two main North American PA lineages (27, 28).…”
Section: Resultsmentioning
confidence: 99%
“…Potentially, the same selection dynamics that create the phylogenetic splits of viral lineages at both the continental (51) and between-flyway (20) levels operate within the MMF and other flyways as well. Studies in the North American Pacific Flyway have shown that populations of viruses in northern breeding locations in Alaska are genetically distinct from populations of viruses circulating in the wintering populations in California (45,46). Some level of competitive exclusion (e.g., host composition or environmental parameters) may operate within the flyway to effectively block migrant lineages from contributing to the dominant lineages circulating in a region (52).…”
Section: Discussionmentioning
confidence: 99%
“…LPAIVs in the MMF. Studies have shown that LPAIVs can be genetically structured within and between North American migratory flyways (20,35,45,46), even in light of relatively high levels of gene flow measured between flyways (19). In the present study, while we observed a pattern of increased dispersal of AIVs within the MMF over short time frames, we also observed signatures of regional persistence of gene diversity across multiple sea- sons, which suggests a temporal effect on the genetic structuring of AIV diversity both within and among flyways.…”
Section: Discussionmentioning
confidence: 99%
“…Within this flyway the dispersal of AIV has potential public health risks. Of the four migratory flyways that encompass North America, the Pacific Flyway has the greatest potential for the introduction of the highly pathogenic AIV of the lethal H5N1 subtype by wild birds due to overlap with birds from Asia where outbreaks occur frequently (Winker et al 2007, Koehler et al 2008, Pearce et al 2009). Although trans-hemispheric gene flow appears to be relatively rare, invasion of a Eurasian subtype hemagglutinin gene has been documented within the Pacific Flyway.…”
Section: Introductionmentioning
confidence: 99%